A NiCo2O4 nanosheet-mesoporous carbon composite electrode for enhanced reversible lithium storage. (April 2016) - Fan, Zhaoyang; Wang, Baorui; Xi, Yingxin; Xu, Xin; Li, Mingyan; Li, Jun; Coxon, Paul; Cheng, Shaodong; Gao, Guoxin; Xiao, Chunhui; Yang, Guang; Xi, Kai; et al.
Abstract: As a member of the ternary metal oxide family, nickel cobaltite is considered as a promising electrode material. This is due to its high theoretical capacity, low diffusional resistance to protons, ease of electrolyte penetration, superior ionic/electronic conductivity and higher electrochemical activity compared to single metallic oxides such as NiO or Co3 O4 . However, NiCo2 O4 's relatively low electrical conductivity and its tendency to pulverize due to the volume changes experienced during the charge–discharge process remain a pressing issue to be solved. Here we demonstrate a simple co-precipitation and calcination routine to graft ultrathin NiCo2 O4 nanosheets onto highly-ordered mesoporous carbon CMK-3 to form a new mesoporous-nanosheet structure which can accommodate stresses induced by volume changes and provide favourable conducting paths. The material exhibits a high specific surface area and excellent electrochemical performance, which can be ascribed to the ultrathin NiCo2 O4 nanosheets and the interconnected conductive network of the mesoporous matrix. The nanosheets and the inner channels of CMK-3 are more beneficial to the diffusion of Li + while the interconnected conductive network favours fast electron conduction.